SUATU TINJAUAN MENGENAI KOPERASI UNIT DESA DAN KOPERASI SERBA USAHA DOSEN GADJAH MADA DILIHAT DARI STRUKTUR ORGANISASI, KEUANGAN DAN LAINNYA - H. R. E. Djarkasih Satiakusumah (Journal of Indonesian Economy and Business (JIEB), 2003)
Recently village Unit Cooperatives (KUD) as one kind of cooperatives to still unable to give sufficient economic services to the community and to realize its role in the national economy, since it still faces various obstacles, both internally and externally, it was necessary to increase the participation by their members.The writer also analyses KOSUDGAMA, to find out the differences of the businesssuccess of the two cooperatives in 2001 and 2002.So a comparative study to KOSUDGAMA in Yogyakarta by managers of KUD in West Java Province need to be done to obtain the experience of other cooperative in running business success.Keywords: Village Unit Cooperatives (KUD), KOSUDGAMA, Participation, Comparative Study, Business success.